Probucol Protects Against Atherosclerosis Through Lipid-lowering and Suppressing Immune Maturation of CD11c+ Dendritic Cells in STZ-induced Diabetic LDLR−/− Mice. Issue 6 (June 2015) - Zhu, Hong; Jin, Xueting; Zhao, Jingjing; Dong, Zhen; Ma, Xin; Xu, Fang; Huang, Wei; Liu, George; Zou, Yunzeng; Wang, Keqiang; Hu, Kai; Sun, Aijun; et al.
Abstract : Abstract: Probucol, an agent characterized by lipid-lowering and antioxidant property, retards atherosclerosis effectively. To test the hypothesis that probucol might act its antiatherosclerotic role by suppressing immune maturation of dendritic cells (DCs), 7-week-old LDLR −/− mice were rendered diabetic with streptozotocin (STZ) and then fed either a high-fat diet only or added with 0.5% (wt/wt) probucol for 4 months, and human monocyte-derived dendritic cells were preincubated with or without probucol and stimulated by oxidized low-density lipoprotein. In STZ-induced diabetic LDLR −/− mice, probucol treatment significantly lowered plasma total cholesterol and high-density lipoprotein-cholesterol levels; regressed aortic atherosclerotic lesions; reduced splenic CD40, CD80, CD86, MHC-II expression, and plasma IL-12p70 production; and decreased the expression of CD11c + DCs within atherosclerotic lesions. In vitro, oxidized low-density lipoprotein promoted human monocyte–derived dendritic cells maturation; stimulated CD40, CD86, CD1a, HLA-DR expression; increased tumor necrosis factor-α production; and decreased IL-4 production. However, these effects were obviously inhibited by probucol pretreatment. In conclusion, our study indicated that probucol effectively retarded atherosclerosis at least partly through lipid-lowering and inhibiting immune maturation of CD11c + DCs in STZ-induced diabetic LDLR −/− mice.